2005
DOI: 10.1152/ajplung.00273.2004
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant phospholipid changes after antigen challenge: a role for phosphatidylglycerol in dysfunction

Abstract: In asthma, inflammation-mediated surfactant dysfunction contributes to increased airway resistance, but the mechanisms for dysfunction are not understood. To test mechanisms that alter surfactant function, atopic asthmatics underwent endobronchial antigen challenge and bronchoalveolar lavage (BAL). BAL fluids were sequentially separated into cells, surfactant, and supernatant, and multiple end points were analyzed. Each end point's unique relationship to surfactant dysfunction was determined. Our results demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 33 publications
1
52
1
Order By: Relevance
“…It has also been observed that children with asthma have higher levels of PC32:0 in sputum compared with control subjects [23]. In atopic asthma, experimental antigen exposure has been shown to induce a reduction in PG in large surfactant aggregates collected from BAL [24]. Leakage of plasma proteins seems to be important for inactivation of 610 620 630 640 650 660 670 680 690 700 710 720 730 740 750 760 770 780 790 800 810 820 830 840 850 860 m/z surfactant [19,21,25].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been observed that children with asthma have higher levels of PC32:0 in sputum compared with control subjects [23]. In atopic asthma, experimental antigen exposure has been shown to induce a reduction in PG in large surfactant aggregates collected from BAL [24]. Leakage of plasma proteins seems to be important for inactivation of 610 620 630 640 650 660 670 680 690 700 710 720 730 740 750 760 770 780 790 800 810 820 830 840 850 860 m/z surfactant [19,21,25].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the possibility that phospholipid itself might participate has been less studied. However, some evidence indicate that surfactant is dysfunctional in asthma with diminished PG content, relative loss of PC as well as increasd lysophospholipids (57). It has been suggested that in antigenchallenged patients, secreted phospholipase A2 could participate in surfactant dysfunction, since sPLA2 exhibit preference for PGs over PCs.…”
Section: Surfactant Pg In Attenuation Of Pathogen-related Inflammatormentioning
confidence: 99%
“…In idiopathic pulmonary fibrosis, ARDS, and asthma, several groups reported decreased unsaturated PG in surfactant (18,(52)(53)(54)(55)(56)(57). The issues of cause and effect in the above diseases remain unclear, but any condition that results in reduced levels of unsaturated PG pools within the lung is likely to increase the susceptibility to inflammatory processes elicited through TLR4 activation.…”
Section: Phospholipid Antagonism Of Lps-induced Inflammationmentioning
confidence: 99%